2006
DOI: 10.1093/her/cyl127
|View full text |Cite
|
Sign up to set email alerts
|

The costs of a community-based intervention to promote maternal health

Abstract: The costs of community-level interventions are rarely reported, although such insights are needed if intervention research is to be useful to practitioners seeking to understand what might be involved in replicating interventions in different contexts. We report the costs of a 2-year community-based intervention to promote the health of recent mothers in Victoria, Australia. Program of Resources, Information and Support for Mothers was an integrated programme of primary care and community-based strategies. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…A further paper was identified during the economic modelling process. 397 It had been excluded at the title and abstract stage as PND or associated terms were not included in the title or abstract. Of the 13 papers identified, 61,174,199,264,[392][393][394][398][399][400] nine described an economic evaluation that was conducted alongside a trial, 53,61,174,199,264,299,392,393,400 three papers described an economic decision model 45,56,394 and one paper described a cost study.…”
Section: Study Selection Criteria and Procedures For The Health Economentioning
confidence: 99%
See 4 more Smart Citations
“…A further paper was identified during the economic modelling process. 397 It had been excluded at the title and abstract stage as PND or associated terms were not included in the title or abstract. Of the 13 papers identified, 61,174,199,264,[392][393][394][398][399][400] nine described an economic evaluation that was conducted alongside a trial, 53,61,174,199,264,299,392,393,400 three papers described an economic decision model 45,56,394 and one paper described a cost study.…”
Section: Study Selection Criteria and Procedures For The Health Economentioning
confidence: 99%
“…The population in the screening papers 45,56 was all postnatal women. For the papers broadly evaluating the prevention of PND, the population differed with some studies including all postnatal women 61,199,264,397 and three studies evaluating women who had been identified as at increased risk of developing PND. 61,174,396 …”
Section: Population Considered In the Health Economics Reviewmentioning
confidence: 99%
See 3 more Smart Citations